1993
DOI: 10.1152/ajpheart.1993.265.5.h1629
|View full text |Cite
|
Sign up to set email alerts
|

Resetting of regional preload due to ventricular shape change alters diastolic and systolic performance

Abstract: The diastolic and systolic pressure of one ventricle is increased by an increase in volume and/or pressure of the opposite ventricle; however, a mechanism for the ventricular interaction remains unclear. We hypothesized that the shape change of one ventricle elicited by the opposite ventricle would lead to resetting of the regional length, which may explain the ventricular interaction. We used 15 cross-circulated isovolumically contracting canine hearts in which both ventricular volumes were independently cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It influences not only the cardiac shape and performance but also patient's prognosis. Deformation of left ventricular shape may also occur in the patient with left and right ventricular pressure and volume overloading [6][7][8][9]. Accordingly, the shape of heart is an important diagnostic and therapeutic index for evaluating a variety of cardiac diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It influences not only the cardiac shape and performance but also patient's prognosis. Deformation of left ventricular shape may also occur in the patient with left and right ventricular pressure and volume overloading [6][7][8][9]. Accordingly, the shape of heart is an important diagnostic and therapeutic index for evaluating a variety of cardiac diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The models (14,15,22) imply that all interactions occur through the septum and are not influenced through the ventricular free walls. We reported that ventricular interdependence not only altered septal position but also caused regional myocardial stretch in the whole ventricle (30,31). For example, increasing RV volume enhanced regional LV diastolic dimensions in the septum and LV free wall, even at constant LV volume and increased LV chamber pressures (30).…”
mentioning
confidence: 96%
“…For example, increasing RV volume enhanced regional LV diastolic dimensions in the septum and LV free wall, even at constant LV volume and increased LV chamber pressures (30). The augmented myocardial diastolic stretch, that is, the increased regional preload, results in the increased resting and active regional forces under the same LV volume, and then the increased forces inevitably elevate LV intracavitary pressure (30,31). Although the septum is important in ventricular interdependence, ventricular interdependence affects the whole heart: the RV free wall, the LV free wall, and the septum (7,30).…”
mentioning
confidence: 99%
See 2 more Smart Citations